Treatment with 5-aminolaevulinic acid methylester is less painful than treatment with 5-aminolaevulinic acid nanoemulsion in topical photodynamic therapy for actinic keratosis - Gholam, Patrick; Weberschock, Tanja; Denk, Katharina; Enk, Alexander (Dermatology, 2011)
Background: Topical photodynamic therapy (PDT) is an excellent treatment option for actinic keratosis (AK). Pain is one of the major adverse effects. Objective: To compare the pain intensity during the extensive treatment of cosmetic units using 5-aminolaevulinic acid methylester (MAL) or 5-aminolaevulinic acid nanoemulsion (BF-200-ALA). Methods: 173 patients with 965 treated areas were enrolled in this retrospective monocentric study. All patients had multiple AKs and received an extensive treatment of the photodamaged area. 424 areas were treated with MAL and 541 with BF-200-ALA. Pain was rated using a standardized visual analogue scale (VAS). The number of PDT treatment interruptions was documented. Results: PDT with MAL led to a lower mean VAS score (5.0 vs. 5.8), a lower number of treatment interruptions (13.2 vs. 19.9%) and a lower amount of patients experiencing severe pain (25.0 vs. 36.0%) compared to PDT with BF-200-ALA. Conclusion: Our data shows that PDT using MAL is less painful than PDT using BF-200-ALA resulting in a significantly lower mean VAS score (p < 0.001), significantly fewer patients experiencing severe pain (p < 0.001) and a significantly (p < 0.05) lower number of treatment interruptions. Differences in selectivity for tumour cells and transport of ALA in peripheral neurons may play a role.
Online veröffentlicht: 12. Juli 2011
Ein Erratum zu diesem Artikel ist veröffentlicht worden: 6. September 2022
Gesehen am 29.11.2023